Halal tourism as a civilizational encounter: Islamic values and cultural accommodation in contemporary Japan - Wahyu Setiawan; Wahyuningsih Supriyani; Amirul Bakhri (PT Perfidia Akademia, 2026)
The development of halal tourism in Japan reflects the country's increasing accommodation of the needs of Muslim travelers. However, studies that explain this phenomenon through the lens of civilizational encounter remain limited. This study aims to analyze how Islamic values are negotiated through the development of halal tourism in Japan from the perspective of civilizational encounter. A qualitative library research approach was employed using thematic analysis of scholarly articles, books, government documents, and official publications issued by the Japan National Tourism Organization (JNTO). The findings demonstrate that the religious needs of Muslim travelers have stimulated both institutional and cultural responses, manifested through the provision of prayer facilities, halal services, and omotenashi-based cultural adaptation, thereby creating a mechanism of civilizational encounter that gives rise to an Inclusive Halal Tourism Ecosystem. This study contributes by proposing the Civilizational Encounter through Halal Tourism conceptual framework as a new perspective for advancing halal tourism studies beyond conventional economic and marketing approaches. Abstrak Perkembangan halal tourism di Jepang menunjukkan semakin meningkatnya akomodasi terhadap kebutuhan wisatawan Muslim. Namun, kajian yang menjelaskan fenomena tersebut sebagai proses civilizational encounter masih relatif terbatas. Penelitian ini bertujuan untuk menganalisis bagaimana nilai-nilai Islam dinegosiasikan melalui perkembangan halal tourism di Jepang dengan menggunakan perspektif civilizational encounter. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kepustakaan (library research) melalui analisis tematik terhadap artikel ilmiah, buku, dokumen pemerintah, dan publikasi resmi Japan National Tourism Organization (JNTO). Hasil penelitian menunjukkan bahwa kebutuhan religius wisatawan Muslim mendorong terbentuknya respons institusional dan respons kultural yang diwujudkan melalui penyediaan fasilitas ibadah, layanan halal, serta adaptasi budaya berbasis omotenashi, sehingga menghasilkan mekanisme civilizational encounter yang membentuk Inclusive Halal Tourism Ecosystem. Penelitian ini berkontribusi dengan menawarkan kerangka konseptual Civilizational Encounter through Halal Tourism sebagai perspektif baru dalam kajian halal tourism.